ANALISIS SPEKTRUM SUARA MANUSIA BERDASARKAN JENIS KELAMIN (GENDER) DAN KELOMPOK UMUR MENGGUNAKAN KOMPUTER - Widia Rahim; Erwin '; Usman Malik (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Research on analysis of human voice spectrum based on gender and age group has been conducted. To record the human voice, it was used a microphone and a computer equipped with a software called “Praat” as a substitute for spectrum analyzer. From the voice spectra, it was obtained the fundamental frequency (pitch) and formant. The sample of the human voice was recorded based on the male and women voice which divided into age group such as children aged 8-11 years, adult 19-23 years and elderly aged above 50 years. In this research, it was used 3 pieces of said, namely “Universitas Riau”, “Selamat Datang” and “Mari Berjuang”. The result of this research indicated that pitch of male was lower than that of women. In general, the relationship between pitch and age showed that the pitch decreases as the age increases. For male, the pitch decreases very significantly from 245,8 Hz to 124,6 Hz as the age increases from children to elderly, while for women the decrease of pitch was linear with small slope. The average formant value for boys is a little bit higher than that of girls which is 525 Hz and 512 Hz respectively. In general, the value of first formant (F1) decreases as the age of human increases.